Multispecies impingement in a tropical power plant, Straits of Malacca - Azila, A.; Chong, V.C. (Elsevier, 2010)
Marine organisms comprised about 70% of the total impinged materials by weight at water intake screens in the Kapar Power Station (KPS), Malaysia The general groupings of `fish', `shrimp', `crab', `cephalopod' and `others' contributed 26% (87 species), 65% (29), 2% (17), 2% (3) and 5% (42) of the total number of impinged organisms, respectively. In general, higher impingement occurred during spring tide, at nighttime and in shallow water The glass perchlet, anchovies, ponyfishes, mojarra, catfishes, haulm!, scat and young croakers were the most vulnerable fishes Vulnerable invertebrates included cephalopods, sea urchin, rockshells and jellyfishes, but penaeid shrimps were the most susceptible in terms of both mortality and body injury Annually. KPS is estimated to kill 85 x 106 marine organisms (42 tons) by impingement This amount, however, is minimal compared to commercial fishery harvests Multispecies impingement at Malaysian power plants poses the problem of finding the best mitigation options for tropical situations (C) 2010 Elsevier Ltd All rights reserved.